Wastewater Treatment Efficiency Using Up flow Anaerobic Filter and Activated Sludge Acclimatization - Lusiana, Uray (Biopropal Industri, 2011)
One of the largest applications of detergent is for cleaning clothes. By society, waste water containing detergent dumped directly into the ground or river. This can lead to pollution of soil or river so that can degrade the quality of the environment. Wastewater treatment has been carried out by the community one of them using the well diffusion because it is cheap. The downside of this treatment is not suitable to be applied in areas with high groundwater level and swampy areas. This study aims to determine the efficiency of wastewater treatment by anaerobic filter and up flow detergent acclimatization activated sludge. Anaerobic system is a biological process that uses the activity of microorganisms that can grow and live in environments without oxygen. Anaerobic bacteria living in the stone surface and oxidized past wastewater. The method used was neutralized waste water until the pH 7 followed by adding it to anaerobic tank and closed.Â  Inside anaerobic tank occurred inoculation by activated sludge and remaining it until 6 days. The temperature then must be watched between 37oC â 40oC in order of successfully acclimatization and itâs indicated by formation of gas. After acclimatization, the wastewater in anaerobic tank was stream down to up flow anaerobic filter through bottom to the top of the tank. The sample was then retaining in 2, 4, 6, 8, 10, 12 and 14 days followed by the detergent content analysis. The result showed that it could degrade the detergent rate from 21,03 mg/L to 3,83 mg/LÂ  and the efficiency until 81,8 % with the maximum retention time was 14 days.